2009
DOI: 10.1002/art.24862
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and osteoarthritis: Is leptin the link?

Abstract: There is significant interest in the correlation between adipose regulators of metabolism, inflammation, and the occurrence of osteoarthritis (OA). In this issue of Arthritis & Rheumatism, Griffin and colleagues report the results of their investigation of the role of leptin (1). The investigators hypothesized that obesity in mice resulting from deletion of the leptin gene (ob/ob) or deletion of the leptin receptor gene (db/db) would result in an increased incidence of knee OA, systemic inflammation, and alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 29 publications
5
28
1
2
Order By: Relevance
“…These findings may be closely related to adipose tissue metabolism, therefore supporting a potential role of adipokines in knee OA structural progression, as suggested by several studies (36)(37)(38)(39)(40)(41)(42)(43)(44)(45). The greater percentage of TKR in a subgroup of patients was also an interesting finding that merits further exploration.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These findings may be closely related to adipose tissue metabolism, therefore supporting a potential role of adipokines in knee OA structural progression, as suggested by several studies (36)(37)(38)(39)(40)(41)(42)(43)(44)(45). The greater percentage of TKR in a subgroup of patients was also an interesting finding that merits further exploration.…”
Section: Discussionsupporting
confidence: 70%
“…However, the finding that an increase in this muscle fat content over time was associated with reduced cartilage volume independent of baseline BMI tempers that hypothesis. Nonetheless, it may be that fatty tissue within the VM may itself produce factors such as adipokines, which in turn might, at least partly, contribute to the worsening of OA symptoms or cartilage degradation (36)(37)(38)(39)(40)(41)(42)(43)(44)(45). In addition, the data showing that in knee OA the quadriceps muscle exhibits atrophy of type 2 fibers (46) could explain the increased fat in the muscle by facilitating fat infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…16 In the present study, the BMI was normal-high, and the serum leptin concentration was correlated with an increase in the total fat mass. The relationship between obesity and OA is an important public health issue.…”
Section: Discussionsupporting
confidence: 52%
“…The current study showed a significant correlation between serum leptin and BMI. Revising literature, serum leptin was elevated in obese persons and correlated with the percent of body fat [13,14,22], also leptin concentration decreased after weight loss [22]. High serum and synovial leptin in obese patients with OA were thought to control local inflammatory processes [23].…”
Section: Discussionmentioning
confidence: 99%